Lactic acid induced microRNA-744 enhances motility of SiHa cervical cancer cells through targeting ARHGAP5. (25th January 2019) - Li, Chao; Jia, Linyan; Yu, Yongsheng; Jin, Liping
Abstract: High-risk (hr) human papillomaviruses (HPV) infection and integration has caused the majority of cervical cancer, of which E6 and E7 oncogenes are invariably retained and expressed to immortalize cells probably via affecting cell migration and invasion, and tumor metastasis. However, the underlying mechanism that mediates the procedure such as motility of cervical cancer cells within the tumor microenvironment is not well understood. Herein, we examined one possible factor—extracellular lactic acid, an end up chemical in glycolytic tumor cells, on the motility in HPV16 positive SiHa cells. The results showed that lactic acid enhanced cell migration and invasion behavior via stimulating the expression of miR-744. ARHGAP5 was confirmed to be a target of miR-744, and silencing ARHGAP5 exhibited an inhibiting effect on cell migration and invasion as that observed by suppressing miR-744. In addition, lactic acid down-regulated E6 and E7 protein levels, and overexpression of either miR-744 or ARHGAP5 could also reduce E6 and E7 levels. Overall, our findings suggest that the miR-774/ARHGAP5 axis may provide a vital role in triggering lactic acid-induced migration and invasion in SiHa cells, regardless of the diminished effect due to the partial inhibition of E6 and E7 expression. Highlights: MiR-744 is significantly upregulated in lactic acid-stimulated SiHa cervical cells. Increased miR-744 level down-regulates E6 and E7 protein levels. Increased miR-744 level promotes migration and invasion of SiHa cells. MiR-744 exerts its effects by targeting ARHGAP5 promoter region. Silencing ARHGAP5 or miR-744 abolished the enhanced migration and invasion behavior.